2012
DOI: 10.5433/1679-0359.2012v33supl2p3265
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania amazonensis em cão com quadro clínico de leishmaniose visceral no Estado do Paraná, Brasil – relato de caso

Abstract: ResumoAs leishmanioses são antropozoonoses que envolvem diversas espécies de Leishmania e hospedeiros, tendo apresentações clínicas variáveis e consideradas de grande importância para a saúde pública. Este artigo descreve um caso de leishmaniose canina causada por Leishmania amazonensis, proveniente da cidade de Cambé, Paraná -Brasil. Este estado é considerado endêmico para a leishmaniose tegumentar americana (LTA) em humanos, porém este é o primeiro relato em cão na região, provocado pela L. amazonensis. A ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
0
4
1
8
Order By: Relevance
“…amazonensis has been described in Brazil, among domestic dogs in São Paulo and Paraná (LAINSON, 2010;TOLEZANO et al, 2007;HOFFMANN et al, 2012). The T. gondii occurrence rate found among the dogs sampled in the present study (61.6%) was lower than the rates of 76.5% and 69.8% that were observed, respectively, among dogs in the urban area of Monte Negro, Rondônia (CAÑÓN-FRANCO et al, 2004) and in urban and rural areas of the state of Pará (VALADAS et al, 2010), which are both in the Amazon region.…”
Section: Occurrences Of Leishmaniasis Have Been Correlatedcontrasting
confidence: 77%
See 1 more Smart Citation
“…amazonensis has been described in Brazil, among domestic dogs in São Paulo and Paraná (LAINSON, 2010;TOLEZANO et al, 2007;HOFFMANN et al, 2012). The T. gondii occurrence rate found among the dogs sampled in the present study (61.6%) was lower than the rates of 76.5% and 69.8% that were observed, respectively, among dogs in the urban area of Monte Negro, Rondônia (CAÑÓN-FRANCO et al, 2004) and in urban and rural areas of the state of Pará (VALADAS et al, 2010), which are both in the Amazon region.…”
Section: Occurrences Of Leishmaniasis Have Been Correlatedcontrasting
confidence: 77%
“…Epidemiological studies have reported the presence of dogs as a risk factor for bovine neosporosis (PARÉ et al, 1998;SAWADA et al, 1998;WOUDA et al, 1999 LAINSON, 2010). Moreover, dogs can be infected by L. amazonensis, which is one of the cutaneous leishmaniasis causal agents (TOLEZANO et al, 2007;HOFFMANN et al, 2012). In Brazil, cutaneous leishmaniasis is a disease of great public health importance, with clinical features ranging from an unapparent form to cases of mucosal and cartilage injury (BRASIL, 2010;GRAMICCIA;GRADONI, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These studies, which recorded lower rates of seropositivity in animals, are similar to the present investigation in their use of random sampling in non-endemic areas and cities. Hoffmann et al (2012) reported the clinical form of VL in a dog from the city of Cambé, Paraná, detecting the presence of L. amazonensis using the multilocus enzyme electrophoresis technique. The animal showed clinical signs consistent with the visceral form of the disease, such as polyarthritis and progressive weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…Zulpo et al (2012) and Caldart et al (2015) studied animals from Londrina and found 11.6% (13/112) and 1.2% (3/236) of seropositivity using IFAT method with 1:40 as a cutoff, respectively; the low prevalence of 1.2% found by the authors may be explained because this study population consisted of clinically healthy animals undergoing elective castration surgery. Pittner et al (2009) (CASTRO et al, 2007;PEREIRA, 2005, HOFFMANN et al, 2012. Several phlebotomine species are present in the same State, and the dominant vector species found infected is Nyssomyia whitmani (MEMBRIVE et al, 2004;OLIVEIRA et al, 2000) wich is involved in the transmission of L. (V.) braziliensis; however, L. (L.) amazonensis vectors have never been found in Paraná.…”
Section: Discussionmentioning
confidence: 99%